2020
DOI: 10.1146/annurev-ento-011019-025032
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Size Dimorphism: Evolution and Perils of Extreme Phenotypes in Spiders

Abstract: Sexual size dimorphism is one of the most striking animal traits, and among terrestrial animals, it is most extreme in certain spider lineages. The most extreme sexual size dimorphism (eSSD) is female biased. eSSD itself is probably an epiphenomenon of gendered evolutionary drivers whose strengths and directions are diverse. We demonstrate that eSSD spider clades are aberrant by sampling randomly across all spiders to establish overall averages for female (6.9 mm) and male (5.6 mm) size. At least 16 spider eSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 145 publications
3
51
0
Order By: Relevance
“…This agrees with our pattern where spider genera with larger body size tend to be species poor, and have generally narrower geographic distributions. We interpret this recovered pattern to be consistent with the predictions of the hypothesis that extreme phenotypes might decelerate speciation and/or cause extinction [59].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This agrees with our pattern where spider genera with larger body size tend to be species poor, and have generally narrower geographic distributions. We interpret this recovered pattern to be consistent with the predictions of the hypothesis that extreme phenotypes might decelerate speciation and/or cause extinction [59].…”
Section: Discussionsupporting
confidence: 87%
“…A female-biased SSD is highly pronounced in certain groups of spiders, notably orbweavers [60]. Kuntner and Coddington [59] hypothesize that extreme phenotypes may represent evolutionary dead-ends. Although, as speculated above, size may fit this prediction, it seems that SSD as a derived ratio does not.…”
Section: Discussionmentioning
confidence: 99%
“…Because eye size is a major factor influencing visual performance (Cronin et al, 2014;Kirschfeld, 1976;Land and Nilsson, 2012), body size increases that lead to eye size increases could be utilized for VA improvements (Corral-López et al, 2017). Based on the prevalence of sexual size dimorphisms throughout many animal groups (Kuntner and Coddington, 2020;Lislevand et al, 2007;Parker, 1992;Teder, 2014), VA differences between the sexes may be an under-documented ---yet not uncommon --phenomenon that warrants further consideration and exploration. and 2) been based on smaller sample sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Strong sexual dimorphism in size with large females and small males occurs in many orb web spiders (Foellmer and Moya-Larano 2007;Robinson and Robinson 1973). The most extreme case of reversed sexual size dimorphism among terrestrial animals can be found in the family Nephilidae (Kuntner and Coddington 2020), where tiny males enter the web of a giant female for mating, which then -more often than not -ends with him being a mate and a meal. Spider species with larger males than females are rare (e.g., Lycosidae: Aisenberg et al 2007;Pholcidae: Huber et al 2013;Argyroneta aquatica: Schütz and Taborsky 2003).…”
Section: Morphologymentioning
confidence: 99%